Clustering Analysis on Ottoman Waqf Studies - Rusydiana, Aam Slamet; Lila, Nazan (SMART Insight, 2025)
This article aims to scan and classify Ottoman waqf studies by cluster analysis method, and fill the gap in the literature. In addition, this study is expected to be a guiding resource for those who want to do research on Ottoman waqfs.In the study, Scopus database was scanned using the keywords